Compostos heterometálicos. Interação do tricarbonil com ligação W-Hg, [WCl(CO)3(bipy)(HgCl)], com tiouréias - Muraoka, T. K.; Mauro, Antonio Eduardo [UNESP]; Nogueira, Vânia Martins [UNESP]; Haddad, P. S. (Editora Unesp, 1997)
Reactions of [WC1(CO)(3)(bipy)(HgCl)], [bipy = 2,2 -bipyridine], with thioureas were performed giving compounds of the type [WCl(CO)(3)(bipy)(HgCl)L], [L = thiourea (tu); N-methylthiourea (mtu); N,N-dimethyithiourea (dmtu)] in which the coordination sphere of the tungsten atom remained unchanged. The coordination of the thioureas to mercury atom was proved to occur in accord to infrared spectra, through the sulphur atom.
Heterometallic compounds. Interaction of the tricarbonyl containing W-Hg bond, [WCl(CO)(3)(bipy)(HgCl)], with thioureas.
Keywords: heterometallic; tricarbonyl; thiourea; infrared spectroscopy